Polymer Nanoparticles Encased in a Cyclodextrin Complex Shell for Potential Site‐ and Sequence‐Specific Drug Release. (5th May 2014) - Ruiz‐Esparza, Guillermo U.; Wu, Suhong; Segura‐Ibarra, Victor; Cara, Francisca E.; Evans, Kurt W.; Milosevic, Miljan; Ziemys, Arturas; Kojic, Milos; Meric‐Bernstam, Funda; Ferrari, Mauro; Blanco, Elvin
<x xml:space="preserve">Abstract</x> Time‐staggered combination chemotherapy strategies show immense potential in cell culture systems, but fail to successfully translate clinically due to different routes of administration and disparate formulation parameters that preclude a specific order of drug presentation. A novel platform consisting of drug‐containing PLGA polymer nanoparticles, stably fashioned with a shell composed of drug complexed with cationic cyclodextrin, capable of releasing drugs time‐ and sequence‐specifically within tumors is designed. Morphological examination of nanoparticles measuring 150 nm highlight stable and distinct compartmentalization of model drugs, rhodamine and bodipy, within the core and shell, respectively. Sequential release is observed in vitro, owing to cyclodextrin shell displacement and subsequent sustained release of core‐loaded drug, kinetics preserved in breast cancer cells following internalization. Importantly, time‐staggered release is corroborated in a murine breast cancer model following intravenous administration. Precise control of drug release order, site‐specifically, potentially opens novel avenues in polychemotherapy for synergy and chemosensitization strategies.